Reform and practice of the cross-integration teaching model: A case study of visual communication design. - Jian Wang; Haizhou Liu (PLoS ONE)
In the context of digitalization, how to effectively carry out interdisciplinary teaching in the field of visual communication design (VCD) to enhance students' comprehensive innovation ability and interdisciplinary collaboration skills has become one of the key issues in the current educational reform. Based on STEAM education, this study constructed a cross-integration teaching model (CITM) for VCD from four aspects: top-level design of curriculum, innovations in teaching methods and approaches, integration of interdisciplinary teaching teams and industry resources, and optimization of evaluation and feedback mechanism. This study adopted the action research, taking the Brand and User Experience Design course as a case example. Data were collected through classroom observation, interviews, questionnaires and team discussions, and multi-dimensional qualitative analysis was conducted using triangulation. The study found that the CITM effectively improved students' innovative thinking, interdisciplinary collaboration and practical abilities, and students showed a high level of acceptance of project-based teaching and co-teaching by multiple teachers. However, the study also revealed that some students still faced difficulties in understanding interdisciplinary theory, and the coordination and coherence of teacher team collaboration need to be further enhanced. It is necessary to further optimizing the communication and collaboration mechanisms of teaching team, strengthening the connection of course content, and continuously introducing industry resources to enhance the application of the model in broader educational contexts.